Best practice guidelines in managing the craniofacial aspects of skeletal dysplasia - Savarirayan, Ravi (Orphanet J Rare Dis, 2021)
BACKGROUND: Recognition and appropriate management of the craniofacial manifestations of patients with skeletal dysplasia are challenging, due to the rarity of these conditions, and dearth of literature to support evidence-based clinical decision making. METHODS: Using the Delphi method, an international, multi-disciplinary group of individuals, with significant experience in the care of patients with skeletal dysplasia, convened to develop multi-disciplinary, best practice guidelines in the management of craniofacial aspects of these patients. RESULTS: After a comprehensive literature review, 23 initial statements were generated and critically discussed, with subsequent development of a list of 22 best practice guidelines after a second round voting. CONCLUSIONS: The guidelines are presented and discussed to provide context and assistance for clinicians in their decision making in this important and challenging component of care for patients with skeletal dysplasia, in order standardize care and improve outcomes.